2018
DOI: 10.4103/2303-9027.193570
|View full text |Cite
|
Sign up to set email alerts
|

The role of endoscopic ultrasound in a case of lung cancer with jaundice

Abstract: Lung cancer is one of the major causes of death in the world. Small cell carcinoma is the most aggressive type and can spread rapidly. The association of a small cell carcinoma with hepatic hilar metastasis and biliary obstruction is rare. Endoscopic ultrasound allows the aspiration of a cytology sample from adenopathies for diagnostic purpose. We present the case of a patient with lung cancer, with lymph node metastasis to the hepatic hilum and extrinsic biliary tree compression. Endoscopic ultrasound allowed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Small cell lung cancer presents initially with increased serum bilirubin in about 10% of cases, caused by hepatic (6%) or pancreatic (4%) metastases[ 94 ]. Obstructive jaundice due to hilar lymph node compression from metastatic small cell lung carcinoma has also been reported[ 95 ]. Most reports of metastasis-induced acute pancreatitis come from small cell lung cancer or gastric cancer metastasizing to the pancreatic head, with isolated reports of squamous cell lung cancer, adrenocortical carcinoma, and breast cancer[ 96 - 99 ].…”
Section: Primary Malignanciesmentioning
confidence: 99%
“…Small cell lung cancer presents initially with increased serum bilirubin in about 10% of cases, caused by hepatic (6%) or pancreatic (4%) metastases[ 94 ]. Obstructive jaundice due to hilar lymph node compression from metastatic small cell lung carcinoma has also been reported[ 95 ]. Most reports of metastasis-induced acute pancreatitis come from small cell lung cancer or gastric cancer metastasizing to the pancreatic head, with isolated reports of squamous cell lung cancer, adrenocortical carcinoma, and breast cancer[ 96 - 99 ].…”
Section: Primary Malignanciesmentioning
confidence: 99%
“…In addition, contrast-enhanced ultrasound increased the diagnostic rate via observation of microvessel density and vascular endothelial growth factor expression, which may be valuable in the evaluation of early-stage breast cancer (17). In addition, microbubble ultrasound contrast agent has been reported to enhance the diagnostic rate for patients with suspected lung cancer in clinical settings (18,19). These reports suggested that microbubble ultrasound contrast not only increases reflected signal, but also improves the diagnostic rate for patients with suspected lung cancer in the clinic.…”
Section: Introductionmentioning
confidence: 99%